A Submucosal Moderately Poor Differentiated Laryngeal Squamous Cell Carcinoma Presenting as a Thyroid Mass: A Report of a New Case - Zhihan Liu; Meng Lei; Ruimin Zhao; Xiaobao Yao; Yanxia Bai; Shaoqiang Zhang (Case Reports in Otolaryngology)
Conclusion: SLC should be taken into consideration in the case of suspicious TC with laryngeal cartilage infiltration and subglottic area infiltration. Further coarse needle puncture or surgical biopsy should be carried out to clarify diagnosis to optimize treatment strategy.